2014
DOI: 10.1242/dev.115048
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing an endogenous degradation system for rapid and targeted depletion ofC. elegansproteins

Abstract: The capability to conditionally inactivate gene function is essential for understanding the molecular basis of development. In gene and mRNA targeting approaches, protein products can perdure, complicating genetic analysis. Current methods for selective protein degradation require drug treatment or take hours for protein removal, limiting their utility in studying rapid developmental processes in vivo. Here, we repurpose an endogenous protein degradation system to rapidly remove targeted C. elegans proteins. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
175
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(189 citation statements)
references
References 67 publications
(84 reference statements)
7
175
0
Order By: Relevance
“…An analysis of degradation kinetics for two in situ-tagged targets, GFP::MAD-1 and GFP:: PP1 , in the embryonic intestine revealed that GFP::MAD-1 was degraded with a half-life of ∼6 min, whereas GFP::PP1 GSP-2 , which is more abundant and cytoplasmic/nucleolar rather than nuclear, was degraded with an ∼40 min half-life. These degradation rates are comparable with rates published previously for ZF1 degron-tagged fusions targeted by ZIF-1 expression (15-30 min half-life; Armenti et al, 2014), auxin-inducible degradation (∼20 min half-life; Zhang et al, 2015) and sortase-based F-box ligation-mediated degradation (∼1 h half-life; Wu et al, 2017). Thus, degradation rates will differ between targets depending on abundance and accessibility, but are likely to be comparable for the different methods.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…An analysis of degradation kinetics for two in situ-tagged targets, GFP::MAD-1 and GFP:: PP1 , in the embryonic intestine revealed that GFP::MAD-1 was degraded with a half-life of ∼6 min, whereas GFP::PP1 GSP-2 , which is more abundant and cytoplasmic/nucleolar rather than nuclear, was degraded with an ∼40 min half-life. These degradation rates are comparable with rates published previously for ZF1 degron-tagged fusions targeted by ZIF-1 expression (15-30 min half-life; Armenti et al, 2014), auxin-inducible degradation (∼20 min half-life; Zhang et al, 2015) and sortase-based F-box ligation-mediated degradation (∼1 h half-life; Wu et al, 2017). Thus, degradation rates will differ between targets depending on abundance and accessibility, but are likely to be comparable for the different methods.…”
Section: Discussionsupporting
confidence: 86%
“…Of the described methods for conditional protein degradation in C. elegans (this report; Armenti et al, 2014;Wu et al, 2017;Zhang et al, 2015), each has advantages and limitations. The auxininducible degron enables simultaneous spatial (via tissue-specific expression of the TIR1 adaptor) and temporal (timing of auxin addition) control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…viable alleles that partially suppress the effect of the MEI-1/MEI-2 katanin: tba-2(sb25) (E277K change), tba-2(sb27) (E194K change), tbb-2(sb26) (E439K change); the mutation tbb-2(sb26) has been used along with mei-1 or mei-2 mutations to probe the functions of MTs in the excretory canal (Shaye and Greenwald, 2015); iv. A targeted degradation strategy to overcome the essential function of GIP-2, which is part of the g-tubulin complex has been developed (Wang et al, 2015), by expressing in the epidermis a GFP nanobody::ZIF-1 fusion, ZIF-1 being an E3 ubiquitin ligase substrate-recognition subunit that will target any protein fused to GFP for degradation (Armenti et al, 2014b;Caussinus et al, 2012).…”
Section: Box 2 Tools To Explore Epithelial Mt Functionsmentioning
confidence: 99%